Relationships Between Opioid-Related Hospitalizations and Intimate Partner Violence and Child Maltreatment Hospitalizations in Pennsylvania Across Space and Time - Sumetsky, Natalie (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) and child maltreatment outcomes are markedly associated with substance abuse disorders. However, few studies have explored these serious family violence outcomes in connection to the opioid epidemic or population-level geographic connections between these variables. This study assesses associations of ZIP code-level IPV and child maltreatment hospitalization outcomes with opioid- and alcohol-related diagnoses as well as economic and demographic neighborhood characteristics. We used 11 years (2004?2014) of ZIP code-level Pennsylvania hospital discharge data and U.S. Census neighborhood characteristics data. As nearby ZIP codes are more likely to be similar than those that are distant, we incorporated spatial autocorrelation using conditionally autoregressive Bayesian hierarchical space?time models. There was a positive relationship between ZIP code-level opioid-related diagnoses and both IPV (relative risk 1.061; 95% credible interval [1.015, 1.106]) and child maltreatment (relative risk 1.055; 95% credible interval [1.035, 1.070]) hospitalizations. There was a positive relationship between alcohol-related diagnoses and IPV but not child maltreatment. Higher median household incomes were associated with lower counts of both IPV and child maltreatment hospitalizations. To illustrate geographic heterogeneity of model estimates, posterior distributions were used to compare variability of effects across ZIP codes. Our findings emphasize the secondary implications of the opioid epidemic in the form of family violence within communities.